Use of Instagram as learning media in senior high school - Muhammad Nur Iman Hadiyana Setia; Monica Fajriana (Curricula: Journal of Curriculum Development, 2022)
This study examines using Instagram as an innovative learning tool for high school students. The indicators assessed are the easiness, frequency, and experience that Instagram provides as a learning tool. This study used a qualitative approach and collected data using a questionnaire completed by SMA/SMK/MA/MAK students. The study used a Likert scale by giving weight to each available answer. The weights in each category will be summed and converted into qualitative data. The data will be drawn by counting how many categories of answers from all respondents. The results showed that forty-four point four percent of students who were respondents agreed with Instagram as a learning tool. The results showed that respondents considered Instagram an easy-to-use learning tool. Instagram's position is ideal as a learning tool because students are comfortable using it. Teachers are expected to use Instagram social media more often as a learning tool so that the benefits of using Instagram can be more optimized in supporting student learning achievements.